Kinetics and growth modes of quasi-2d silver branched electrodeposits produced in the presence of a supporting electrolyte - Schilardi, P. L. (1997)
Quasi-2d silver electrodeposits were grown electrochemically at constant potential from aqueous Ag+ ion-containing solutions in the presence of a supporting electrolyte, at room temperature, using a three-electrode quasi-2d circular electrochemical cell. Open branching and dense radial branching patterns were distinguished on the centimetre scale, and growth mode transitions could be observed during the process. Branching patterns exhibited a mass fractal behaviour with a mass fractal dimension increasing from that expected for a DLA-like pattern to that of a dense branching pattern as either the cathodic overpotential (ηc) or the Ag+ ion concentration in the solution (c) was increased. The electrodeposition current increased with time exhibiting different regimes depending on whether an open branching or a dense radial branching growth mode prevailed. When the electrodeposition time exceeded a certain critical value, the radial growth rate of electrodeposits (vr) approached a vr α ηcc relationship. The experimental morphologies and growth kinetics were reproduced by Monte Carlo simulations of a growth model in which depositing particles follow a biased random walk.